Enigmatic Perforated Stone Disk and Grooved Stones from Three Caves Sites in Sumatra - Fauzi, Mohammad Ruly; Simanjuntak, Truman; Forestier, Hubert (Badan Riset dan Inovasi Nasional, 2023)
Ground stone tools, especially perforated stone disks and grooved stones, are rarely discussed in Indonesian prehistory. In terms of its quantity and workmanship, these types of artifacts are fairly unique. They are often limited in quantity, which makes it difficult to compare with the other references. Moreover, their technological aspect still needs to be widely understood by academics. For the first time in Indonesia, this article will discuss perforated stone disks and grooved stones in the context of prehistoric cave sites in Sumatra. Through formal analysis of its attributes at medium to high magnification, we provide a reference for their technological aspects as well as the context of the artifact. Our study reveals that both types of artifacts appear to be closely related to the aquatic culture. The practical function of these artifacts is associated with a fishery tradition on the rivers inland. Our argument is corroborated by the remnants of aquatic fauna associated with these two types of artifacts. Apart from that, the perforated stone disks that were previously reported were found in the mainland of Southeast Asia and, in fact, also found in Sumatra. It further emphasizes the connection between the cultural entities of prehistoric populations that inhabited insular and mainland Southeast Asia.